Processos de criação de interfaces digitais: o usuário como protagonista - Brandão, Camila Calixto Rocca (2013)
On the communication field, specifically on the studies about the creative processes of websites interfaces, the departments of account planning and information architecture/user experience design are responsible for the concept idealization and strategy for the creation and development of the digital interface. During the creative process, one of the most relevant factors is the focus on the user. Especially for sites that are part of advertising communication campaigns, driven to the relationship between brands and their consumers, which final objective is to build loyalty and generate the consumption of brands products and services on the long term. The mapping of users behavior, habits and needs that represent an interface s target, are basis for the tools and functionalities that the site will offer. A deeper and more complete mapping drives a more efficient and richer experience for the interface user. Under this purpose, planning methodologies are used together with user experience design techniques such as user tests and projective techniques, such as the creation of personas personas are fictitious characters created to represent the different real users profiles that are part of the target, defined in demographic, attitudinal and/or behavioral aspects, who will use a site. Having this context in mind, this study aims to analyze the planning process during websites creation, with focus on users mapping and understanding, reflecting on the available methodologies and projective techniques, above all the personas technique, and the impact of using those techniques in the creative process. Therefore, as methodological basis for this study we have done documental and bibliographical researches, and a descriptive presentation of a real case study, for illustrating digital interfaces creative process. The corpus of this study is the planning process for the creation of the new Brazilian Nestlé s website. Analysis period: August/2010 to June/2013. There were used as theoretical foundation concepts of mass communication, culture and consumption, advertising communication and hybrid advertising from Martin-Barbero, Bauman, Fontenelle, Wolf, Pinheiro, Carrascoza, Covaleski; of cyberspace and network creation processes from Castells, Lévy, Manovich, Morin, Deleuze and Guattari, Santaella, Leão, Salles, Lemos; and concepts of information architecture andu ser experience design from Kruger, Cooper, Moggridge, Mulder, Adlin. This study may contribute for the development of planning process typology for the creation of users centered websites, resulting on the development of interfaces capable to deliver an intuitive, interactive and efficient experience to different types of users